Effect of effective microorganisms (EM) on concrete performance - Mohd Amiruddin Bin Roslan (School of Environmental Engineering, University Malaysia Perlis, 2014)
Concrete technology is life-long research. The technology strives to discover the best additives or admixtures that are able to produce good concrete in terms of physical, chemical and mechanical properties in a more economical, sustainable, environmental-friendly and obtainable. Since admixtures for concrete are known to improve the properties of concrete and indirectly increase the strength of concrete, they are now widely used in the construction industry all over the world. Admixtures